An empirical approach to urban land monopoly: A case study of the city of Barranquilla, Colombia. (August 2019) - Garza, Nestor; Lizieri, Colin
In this paper, we focus on the role and economic effect of land ownership and land monopoly in emerging urban environments. Land monopoly in conventional economics is a theoretical 'impossibility' which, nonetheless, allows for a spatial empirical approach. We design a spatial land monopoly test of our own, understood as a pricing strategy where land prices can be 'over and above' those determined by city-wide location, urban regulation and externalities. We use the city of Barranquilla (Colombia) as a case study. This city offers ideal conditions for investigation of theories of land monopoly, given extreme land concentration in its highly regulated elite northern fringe. We found no evidence of land monopoly pricing using different specifications of the spatial tests, which conformed to standard urban economic expectations: the pattern of development pointing to different, political channels influencing development.